IDENTIDADES E TEOLOGIAS NO PRIMEIRO CÂNTICO DO SERVO DE YHWH: Estudo exegético de Isaías 42,1-9 SÃO BERNARDO DO CAMPO 2014 - Pires, Fábio (2014)
The identity of the Servant of YHWH has been always a challenge for biblical research. Who is this Servant? It is not intended to know who historically was the Servant of YHWH, as this is an impossible task. It is intended to raise some clues from the historical context and the actual text of Deutero-Isaiah that leads to consider the possibility that an exile community in Babylon was called servant and destined by YHWH for such a mission. In the passage from Isaiah 42.1 to 9, YHWH calls the Servant for a very specific mission. This right that Servant will come out to the nations is the right to happen for the nations. This is about the law of the Lord, that manifested in the release of all prisoners. The Servant with his silent and prophetic postures, with his solidarity practice to the sufferers and his tenacity will carry forward this project of liberation. Through exegetical procedures and theoretical framework of different authors who have already researched on this topic, it intends to investigate the possibility that this song of the Servant of YHWH arises a Theology of the Servant who is deeply in tune with the Being of YHWH himself. Thus, YHWH - Servant carries the same concrete project of liberation that is founded in the justice and right. Awakens among the suffered people, a new model of political leadership.